Medieval landscapes of Greece and Turkey: a post-colloquium commentary - Bintliff, John (Journal of Greek Archaeology, 2020)
Our colleague Effie Athanassopoulos has done an excellent job in assembling a collection of papers to reflect the current state of the art for Medieval landscape archaeology in the Aegean and Anatolia. One of the shared themes in many of these papers is the state of maturity of this subfield of Mediterranean Archaeology. It echoes a much wider question in post-Roman studies for this large region, as to how progress in this period and area compares to what has been achieved in Western Europe. For example, the limitations of Byzantine Archaeology have repeatedly been raised by some of its practitioners and associated historians since the 1980’s, while Greek Post-Medieval Archaeology has been seen as even more a Cinderella-subject over the same period. To judge by this colloquium, much progress has been made: there is a larger body of researchers, who read each other’s work and share methods and questions to address, yet it is still a small community. In the practice of archaeological survey, recognised as a prime tool for landscape archaeology, we still find recent projects which choose to ignore the surface sites of post-Roman eras (e.g. the Antikythera Project). Nowadays, an excavation which dug away the recent levels to get at the Classical ones would be seen as scandalous, so why should we permit the equivalent to occur in regional survey, where nobody is going to revisit the same fields to compensate for such neglect?